Pengembangan Model Pembelajaran Berbasis Proyek dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam - Dandi Ardiansyah; Abdullah Abdullah (Lembaga Yasin AlSys, 2026)
Although project-based learning in Islamic Religious Education has received attention in various studies, research that specifically discusses the development of Project Based Learning (PjBL) through Classroom Action Research to improve learners’ learning outcomes at the junior secondary school level remains limited. This study aims to analyze the effectiveness of the PjBL model in improving learners’ learning outcomes and participation in Islamic Religious Education learning at SMP Negeri 8 Palangka Raya. This study used a quantitative-qualitative approach with a Classroom Action Research design implemented in two cycles, involving 32 Grade VIII students selected through purposive sampling. Data were collected through observation, interviews, documentation, and learning outcome tests, and were then analyzed using quantitative and qualitative descriptive techniques. The results show that the implementation of PjBL was able to significantly improve learners’ participation and learning outcomes in Islamic Religious Education. The percentage of learning mastery increased from 56.25% in the pre-cycle stage to 75% in Cycle I and reached 90.62% in Cycle II. In addition, learners showed improvements in collaboration, communication, and contextual understanding of Islamic values during the learning process. This finding contributes to the development of innovative learning theory in Islamic Religious Education and broadens understanding of the implementation of contextual learning at the junior secondary school level. The conclusion of this study emphasizes that PjBL plays an important role in increasing learners’ engagement and learning achievement in Islamic Religious Education. The implications of this study provide a practical basis for teachers and schools in implementing collaborative, contextual, and learner-centered learning, while also opening opportunities for further research on the integration of digital learning media and character education in project-based Islamic Religious Education learning.